Chiral separation of benzothiazole derivatives of amino acids using capillary zone electrophoresis. Issue 3 (23rd December 2016) - Nováková, Zuzana; Pejchal, Vladimír; Fischer, Jan; Česla, Petr
Abstract : A method for the separation of enantiomers of leucine and phenylalanine benzothiazole derivatives as potential antimicrobial agents was developed using capillary zone electrophoresis with a dual cyclodextrin (CD) system. The best resolution of enantiomers was achieved in 100 mmol/L phosphate background electrolyte (pH 3.5) with the dual CD system consisting of 10 mmol/L of β‐CD with 10 mmol/L of 2‐hydroxypropyl‐β‐cyclodextrin for leucine derivative and 10 mmol/L of 2‐hydroxypropyl‐γ‐cyclodextrin for phenylalanine derivative, respectively. Under the optimal conditions, the highest enantioresolution of 1.25 was achieved in a noncoated‐fused silica capillary at 17°C and 24 kV applied voltage.